Features of diving reflex in synchronized swimmers - Zemlyanukhina, T. A.; Rybyakova, T. V.; Podyacheva, E. Yu.; Baranova, T. I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to identify the features of diving reflex in synchronized swimmers. Methods and structure of the study. Sampled for the study were 36 female synchronized swimmers of different sport qualifications (masters of sport and first-rank athletes). Their cardiovascular indices were analyzed.